Outcome Analysis of Congenital Diaphragmatic Hernia Cohort before and after Implementation of Standardized Protocol in a Tertiary Neonatal Unit - Sur, Amitava; Awoseliya, Adjemoke; Sharma, Alok (The Surgery Journal, 2017)
Despite evolving evidence and increased understanding, there is a strong argument that best outcomes in managing congenital diaphragmatic hernia (CDH) patients are achieved in centers which have a high admission rate of such patients and follow standardized operating protocols of management. Pneumothorax and air leak syndromes are one of the main causes of pre- and postoperative morbidity in these patients and experts believe that delivery room sedation and gentle ventilation strategies can minimize this. We observed a significant drop in incidence of pneumothorax and reduction of mortality following implementation of standardized guidelines at the neonatal unit at Southampton which is a tertiary-level neonatal care in the southern United Kingdom and a regional referral center for CDH patients.
Keywords: congenital diaphragmatic hernia; pneumothorax; standardized guidelines